ISLAM MODERAT VERSUS TRADISIONAL:TINJAWAN HUKUM DAN PENDIDIKAN - Bulek, Muhammad Jahar; Ridwan, Muhammad; AM, Rusydi; Saputra, Riki; Wahyuni, Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: This article comparatively examines the moderate and traditional Islamic approaches in the realm of law and education. Moderate Islam is characterized by its emphasis on the principles of tolerance, interfaith dialogue, and contextual interpretation of Islamic sources. In contrast, traditional Islam places more emphasis on preserving established and inherited religious practices and interpretations. Through a review of various Islamic legal literature and an analysis of the curriculum structure in Islamic educational institutions, this article evaluates the extent to which the two approaches influence the understanding and implementation of Islamic teachings in society. The research findings indicate that although moderate Islam tends to be more responsive to the dynamics and challenges of the modern era, traditional Islam still plays a significant role in shaping the religious identity and social values of the community. This discussion is expected to contribute to academic understanding of the urgency of creating a balance between the two modes of thought in order to support the creation of a harmonious social order and an inclusive Islamic education system.Keywords: Moderate Islam, Traditional Islam, Law, Education.